Osteoclast‐Derived Autotaxin, a Distinguishing Factor for Inflammatory Bone Loss. Issue 11 (30th September 2019) - Flammier, Sacha; Peyruchaud, Olivier; Bourguillault, Fanny; Duboeuf, François; Davignon, Jean‐Luc; Norman, Derek D.; Isaac, Sylvie; Marotte, Hubert; Tigyi, Gabor; Machuca‐Gayet, Irma; Coury, Fabienne
Abstract : Objective: The severity of rheumatoid arthritis (RA) correlates directly with bone erosions arising from osteoclast (OC) hyperactivity. Despite the fact that inflammation may be controlled in patients with RA, those in a state of sustained clinical remission or low disease activity may continue to accrue erosions, which supports the need for treatments that would be suitable for long‐lasting inhibition of OC activity without altering the physiologic function of OCs in bone remodeling. Autotaxin (ATX) contributes to inflammation, but its role in bone erosion is unknown. Methods: ATX was targeted by inhibitory treatment with pharmacologic drugs and also by conditional inactivation of the ATX gene Ennp2 in murine OCs (Δ ATX C tsk ). Arthritic and erosive diseases were studied in human tumor necrosis factor–transgenic ( hTNF +/− ) mice and mice with K/BxN serum transfer–induced arthritis. Systemic bone loss was also analyzed in mice with lipopolysaccharide (LPS)–induced inflammation and estrogen deprivation. Joint inflammation and bone erosion were assessed by histology and micro–computed tomography. The role of ATX in RA was also examined in OC differentiation and activity assays. Results: OCs present at sites of inflammation overexpressed ATX. Pharmacologic inhibition of ATX in hTNF +/− mice, as compared to vehicle‐treated controls, significantly mitigated focal bone erosion (36% decrease; P < 0.05) and systemic bone loss (43% decrease; P < 0.05), without affecting synovial inflammation. OC‐derived ATX was revealed to be instrumental in OC bone resorptive activity and was up‐regulated by the inflammation elicited in the presence of TNF or LPS. Specific loss of ATX in OCs from mice subjected to ovariectomy significantly protected against the systemic bone loss and erosion that had been induced with LPS and K/BxN serum treatments (30% reversal of systemic bone loss [ P < 0.01]; 55% reversal of erosion [ P < 0.001]), without conferring bone‐protective properties. Conclusion: Our results identify ATX as a novel OC factor that specifically controls inflammation‐induced bone erosions and systemic bone loss. Therefore, ATX inhibition offers a novel therapeutic approach for potentially preventing bone erosion in patients with RA.